# I'm having some trouble and I've not been very good at math, so I need some help with (7x+2)3+8x

lynn30k | Certified Educator

Remember PEMDAS--parentheses, exponents, multiply, divide, add, subtract, in that order. Look at the expression you want to simplify. The first thing to do is multiply both of the variables in the parenthesis by the 3 on the outside. Usually, the 3 would be before the parenthesis, but it doesn't matter here, because you want to multiply before you do anything with the 8x. So:

7x times 3 = 21x      2 times 3 = 6     8x stays 8x

Now you can combine the terms that have 'x'   21x+8x=29x, so your expression becomes 21x + 6

hala718 | Certified Educator

(7x + 2)3 + 8x

Let us use the distribution method :

We know that:

(a+ b)*c = a*c + b*c

==> (7x+2)*3 + 8x = 7x*3 + 2*3 + 8x

==> 21x + 6 + 8x

Now group similar:

==> 29x + 6

jeyaram | Student

(7x+2)3+8x=7*3*x+2*3+8*x

=21x+6+8x

=29x+6

neela | Student

To simplify (7x+2)3+8x.

Multiplication is didtributive over addtion. So (7x+2)3 = 7x*3+2*3= 7*3*x+2*3 =21x+6, as 7x*3 = 7*3*x = 21x by commutative property of multiplication.

Therefore (7x+2)3+8x = 21x+2+8x =21x+8x+6 = (21+8)x +6  =29x+6.

givingiswinning | Student

(7x+2)3+8x

21x + 6 + 8x

29x + 6

atyourservice | Student

(7x+2)3+8x

the first step is to distribute the 3 to the numbers inside the parentheses:

21x + 6 + 8x

now combine like terms (8x and 21x)

29x + 6